Natural radioactivity and mineralogical composition of different particle size fractions of a river sediment from Calabria, southern Italy: a case study. Issue 1 (1st January 2022) - Caridi, F; Acri, G; Belmusto, G; Crupi, V; Faggio, G; Grillo, R; Messina, G; Paladini, G; Venuti, V; Majolino, D
Abstract: The natural radionuclides ( 238 U, 232 Th and 40 K) content and the mineralogical characteristics of three different particle size fractions of a sediment sample from the Amendolea river, Calabria region, southern Italy, were investigated. High Purity Germanium (HPGe) gamma spectrometry was employed for the radioactivity measurements and specific activity data were reported. X-Ray Diffraction (XRD) measurements were carried out to identify the mineral contents of each particle size fraction. This case study was developed with the aim of evaluating the specific activities of natural radionuclides and their relation to specific minerals. Data obtained can provide useful information in view of a deep understanding of the adsorption of radioactive elements and the influence of the sediment granulometry on the radionuclides specific activities.